KARAKTERISASI TIGA STRAIN IKAN GURAME (Osphronemus gouramy Lac.) BERDASARKAN METODE TRUSS MORFOMETRIKS [Characterization of three strains of giant gouramy [Osphronemus gouramy Lac.) based on truss morphometries method] - Lies Setijaningsih; Otong Zenal Arifin; Rudhy Gustiano (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2007)
Objective of the study is to clarify morphometric characters of three giant gouramy strains based on the truss morphometric method. The highest index similarity within strain was in Bastar strain (87.0%) and the lowest was in Blue strain (73.7%). The highest index similarity between strains was between Blue Safire and Bastar strain (15.8%) and the lowest was between Bastar and Blue Safire (4.3%). The correlation values of gouramy characters (combined male and female) tend to close male characters. Five characters (B5, A3, A6, A2, Cl) enabled to be used as discriminators on gouramy.